1995
DOI: 10.2337/diacare.18.4.549
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Erythrocyte Membrane Fluidity in Poorly Controlled IDDM: Influence of ketone bodies

Abstract: The factors that most influence membrane fluidity in IDDM patients appear to be hyperglycemia and ketone bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 9 publications
1
50
1
Order By: Relevance
“…These include increased polyol pathway and associated changes in the intracellular redox state, increased diacylglycerol synthesis with consequent activation of specific protein kinase C (PKC) isoforms, increased nonenzymatic glycation of both intra-and extracellular proteins, and increased oxidative stress (33)(34)(35)(36)(37)(38)(39). Oxidative stress may arise from a variety of mechanisms, such as excessive oxygen radical production as a result of the auto-oxidation of glucose (39), the activation of P-450 -like activity by the glucose metabolite NADPH (36), glycated proteins (40 -42) and the ketone body AA (22)(23)(24)(25)(26), and the depletion of NADH by the activation of aldose reductase (35) and glycation of antioxidative enzymes, which limits their capacity to detoxify oxygen radicals (38). Type 1 diabetic patients may experience oxidative stress from both hyperglycemia and ketosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include increased polyol pathway and associated changes in the intracellular redox state, increased diacylglycerol synthesis with consequent activation of specific protein kinase C (PKC) isoforms, increased nonenzymatic glycation of both intra-and extracellular proteins, and increased oxidative stress (33)(34)(35)(36)(37)(38)(39). Oxidative stress may arise from a variety of mechanisms, such as excessive oxygen radical production as a result of the auto-oxidation of glucose (39), the activation of P-450 -like activity by the glucose metabolite NADPH (36), glycated proteins (40 -42) and the ketone body AA (22)(23)(24)(25)(26), and the depletion of NADH by the activation of aldose reductase (35) and glycation of antioxidative enzymes, which limits their capacity to detoxify oxygen radicals (38). Type 1 diabetic patients may experience oxidative stress from both hyperglycemia and ketosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, ketonemia levels of 1-2 mmol/l (1-2 mol/ml) are frequently seen in diabetic patients, even at the time of routine check-up visits to the clinic (22). It is known that diabetic patients with frequent episodes of ketosis experience an increased incidence of vascular disease, morbidity, and mortality (21)(22)(23). However, the underlying mechanisms by which ketosis promotes vascular disease in type 1 diabetic patients are unclear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the HG study, cells were exposed to a medium having a HG concentration of 25 mM. Many previous studies have reported that glucose concentrations as high as 50 mM have been found in the blood of patients with uncontrolled diabetes (12). It is true that blood glucose levels in patients are not likely to stay as high as 25 mM for 24 h. However, tissue damage in diabetic patients occurs over many years of countless hyperglycemic episodes.…”
Section: Methodsmentioning
confidence: 99%